2011
DOI: 10.1371/journal.pone.0018891
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses to the RTS,S/AS01E and RTS,S/AS02D Malaria Candidate Vaccines Administered According to Different Schedules to Ghanaian Children

Abstract: BackgroundThe Plasmodium falciparum pre-erythrocytic stage candidate vaccine RTS,S is being developed for protection of young children against malaria in sub-Saharan Africa. RTS,S formulated with the liposome based adjuvant AS01E or the oil-in-water based adjuvant AS02D induces P. falciparum circumsporozoite (CSP) antigen-specific antibody and T cell responses which have been associated with protection in the experimental malaria challenge model in adults.MethodsThis study was designed to evaluate the safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 34 publications
3
40
3
3
Order By: Relevance
“…Induction of CD4 + T cells directed against P. falciparum CS protein by RTS,S adjuvanted formulations has been shown in clinical field trials in adults and children. 6,8,9,[21][22][23] No systematic vaccine-induced CD8 + T cell response was detected in PBMCs in our study, which was consistent with other studies that showed RTS,S/AS induces little or no detectable CD8 + T cell response. 6,11,21,24,25 The anti-CS humoral immune responses in this study tended to be lower than those observed following administration of 3 doses of RTS,S/AS01 or RTS,S/AS02 to malaria-experienced children in Africa 13,14 but higher than those in African adults in a high malaria transmission area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Induction of CD4 + T cells directed against P. falciparum CS protein by RTS,S adjuvanted formulations has been shown in clinical field trials in adults and children. 6,8,9,[21][22][23] No systematic vaccine-induced CD8 + T cell response was detected in PBMCs in our study, which was consistent with other studies that showed RTS,S/AS induces little or no detectable CD8 + T cell response. 6,11,21,24,25 The anti-CS humoral immune responses in this study tended to be lower than those observed following administration of 3 doses of RTS,S/AS01 or RTS,S/AS02 to malaria-experienced children in Africa 13,14 but higher than those in African adults in a high malaria transmission area.…”
Section: Discussionsupporting
confidence: 91%
“…[5][6][7] CS-specific CD4 + T cells induced by RTS,S produce a mixture of cytokines, such as interleukin (IL)-2, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ. [7][8][9][10][11] In phase 2 clinical trials of adults and children, the RTS,S/AS01 formulation had an improved immunogenicity profile, in terms of humoral and cell-mediated immune (CMI) responses, and an equally favorable safety profile as compared with RTS,S/AS02. [11][12][13][14] The RTS,S/AS01 formulation was…”
Section: Introductionmentioning
confidence: 99%
“…The choice of adjuvant was reconsidered following evidence in larger studies conducted in adult volunteers, and subsequently in children, of improved CD4 + T-cell responses and improved efficacy when AS01 was used instead of AS02 [41][42][43][44][45]. In a large Phase-3 study, efficacy against any malaria due to P. falciparum over 12 months of follow-up after dose 3 was 31.3% in infants 6-12 weeks of age with coadministration of EPI (Expanded Program on Immunization) vaccines and 55.8% in children 5-17 months of age at the time of the first dose [46].…”
Section: Rtss/as01 Malaria Vaccine Candidatementioning
confidence: 99%
“…It should however be noted that the fourth dose-enhanced VE compared to RTS,S/AS01 vaccinees who didn't receive a fourth dose. The potential of the RTS,S/ AS01 vaccine to predispose to humoral hypo-responsiveness to CS by a mechanism similar to that observed for non-conjugated polysaccharides seems unlikely in view of the characteristics of the CS immune response, mainly the induction of CD4 + T cell [16,21,49] and CS-specific memory B-cell responses [49]. In addition, similar anti-CS antibody kinetics were previously observed with a delayed third vaccine dose when RTS, S/AS01 was given according to a 0,1,7-month schedule in a phase II study [19].…”
Section: Immunogenicitymentioning
confidence: 99%